2017
DOI: 10.1016/j.ijid.2017.05.011
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial storage and antibiotic knowledge in the community: a cross-sectional pilot study in north-western Angola

Abstract: Community interventions for appropriate use of antibiotics should be designed with a special focus on women. This should be done through public awareness campaigns and improving access to reliable medical services. Drug prescribers are key not only to appropriate antimicrobial prescription, but also to adequate dispensing, and are strong advocates for the possible misconceptions on antimicrobial usage by lay people.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 35 publications
3
9
0
Order By: Relevance
“…The limited understanding of the treatment indications of antibiotics found in this study was consistent with existing literature [6,20,47,48]. This was evidenced by the fact that the vast majority were unable to specify the type of agent that antibiotics are effective against, and also that the range of diseases mentioned to be treatable by antibiotics was beyond the scope of antibiotic indication.…”
Section: Discussionsupporting
confidence: 76%
“…The limited understanding of the treatment indications of antibiotics found in this study was consistent with existing literature [6,20,47,48]. This was evidenced by the fact that the vast majority were unable to specify the type of agent that antibiotics are effective against, and also that the range of diseases mentioned to be treatable by antibiotics was beyond the scope of antibiotic indication.…”
Section: Discussionsupporting
confidence: 76%
“…In our study, 42.8% of respondents incorrectly supported the idea that antibiotic treatment should be discontinued as soon as symptoms disappear. This proportion was comparable to those found in Angola (40%) [51] and Malaysia (41.9%) [52], but lower than those found in Kenya (83.6%; 93.4%) [40] and India (65.55%) [53]. The lack of knowledge about antibiotic use could concretely result in the arbitrary cessation of treatment.…”
Section: Discussionsupporting
confidence: 69%
“…Female students and those having at least one parent with higher education were consistently associated with a significantly higher chance of keeping antibiotics at home, both of which support previous studies. Cortez et al [ 56 ] and Ocan et al [ 57 ] reported women as being more likely to keep antibiotics at home, while Awad and colleagues found that higher education levels were associated with a higher possibility of self-medication [ 16 ]. We also found that having a parent working in the medical field promoted home antibiotic storing behaviors.…”
Section: Discussionmentioning
confidence: 99%